The last 10 years: any changes in perceptions of the seriousness of alcohol, cannabis, and substance use in Canada? - John A. Cunningham; Anja Koski-Jännes (BMC, 2019)
Abstract Background Over the last decade, there have been a number of changes in the Canadian landscape - the deconstruction of alcohol policy in some provinces, the legalization of cannabis, increased availability of gambling options, and the increase in opioid use and its associated problems. Have there been concomitant changes in societal images of addictions? Methods A general population survey on societal images of addictions was conducted in multiple countries in 2008 - Finland, Sweden, Canada (Canadian sample size: N = 864; 40% response rate), and part of Russia (St Petersburg). We repeated the same survey in 2018 in Canada (N = 813; response rate = 23%). The survey assessed perceptions of the seriousness of different issues to society - including items about alcohol, tobacco, marijuana, gambling, misuse of medical drugs, and drugs like amphetamine, cocaine, or heroin - among other items (e.g., pollution, violent crime, prostitution). Results There were increases in perceptions of the seriousness of misuse of medical drugs (p = .001), of illicit drugs (p = .005), ratings of the seriousness of cannabis use (p = .02), and a decrease in ratings of gambling as a social problem (p = .04). Ratings of the seriousness of alcohol and tobacco as social problems did not display significant changes over time (p > .05). Conclusions There has been some variation in societal perceptions of the seriousness of different addictions. Increases in perceptions of the seriousness of misusing medical drugs and the use of illicit drugs may reflect increases in societal concerns about opioid use and its associated problems. Despite substantial changes in alcohol control policies, the legalization of cannabis, and the increased availability of options for gambling, there appears to be very little associated change in societal perceptions regarding these addictive behaviours.